The Effect Of Work Motivation And Work Environment On The Performance Of Administrative Staff At Mts Nwdi School - Selina Farhiyani; Mispandi; Pahrudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to determine and analyze the influence of work motivation and work environment on the performance of school administrative staff at Madrasah Tsanawiyah (MTs) in the NWDI environment. This study was motivated by the discovery of several problems in the performance of administrative staff, such as late completion of work, lack of accuracy in administrative management, and less than optimal utilization of work facilities. The study used a quantitative approach with an associative method to determine the relationship and influence between variables. The population in this study was all administrative staff at MTs NWDI with a sample of 100 respondents determined using the Paul Leedy formula and simple random sampling technique. Data collection was carried out through a questionnaire with a Likert scale (1–5), while data analysis used validity and reliability tests, multiple linear regression, t-tests, and F-tests with the help of IBM SPSS. The results showed that work motivation had a positive and significant effect on the performance of administrative staff with a calculated t-value of 3.413 > t-table 1.660 and a significance value of 0.001 < 0.05. The work environment also has a positive and significant effect on performance with a calculated t value of 2.549 > t table 1.660 and a significance value of 0.004 < 0.05. Simultaneously, work motivation and work environment have a significant effect on the performance of administrative staff with a calculated F value of 11.482 > F table 3.09 and a significance value of 0.000 < 0.05. Thus, good work motivation and work environment can improve the performance of school administrative staff optimally.